One-Pot Pyridinium-Ylide-Assisted Tandem Reaction for the Diastereoselective Synthesis of trans-2,3-Dihydrofuran–Chromone Conjugates - Das, Supratim; Mandal, Subham; Mukhopadhyay, Chhanda (Synlett, 2025)
An efficient procedure for the preparation of novel fused 2,3-dihydrofuran–chromone conjugates was developed with the assistance of a pyridinium ylide generated in situ. Pyridine, a 3-formylchromone, a cyclohexane-1,3-dione, and a phenacyl bromide, with triethylamine acting as a catalyst, underwent a sequential, one-pot, two-step, tandem reaction that proceeded smoothly in aqueous media. 1H and 13C NMR spectroscopy and single-crystal analysis confirmed the diastereoselective synthesis of trans-2,3-dihydrofurans.
Keywords: metal-catalyst-free reaction; aqueous medium; dihydrofuran–chromone conjugates; gram-scale preparation; pyridinium ylides; one-pot reaction